Study of posterior vaginal wall prolapses and correlation with bowel function - Bijwe, Smita Anand; Rajbhara, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study’s objectives were to describe symptoms related to bowel symptoms in women with prolapse and to compare these symptoms as per the grading of posterior vaginal prolapse. Methods: Descriptive study, 63 women answered questionnaire for assessment of bowel function and were subjected to physical examination according to the International Continence Society’s system for grading uterovaginal prolapse. Results: The distribution of pelvic organ support by overall POPQ stage was 6.4%stage 1,21%stage 2, 50% stage 3, and 23% stage 4. Women were asked to rate the extent to which they were bothered by their bowel function on a scale of 1 to 10, with 1 being not at all and 10 being extremely. Thirty-six women (58%) reported 1 to 4, 18 (29%) reported 5 to 7, and 8 (13%) reported greater than 8. According to the furthest extent of posterior vaginal prolapse at point Bp, 22 (15.5%) were in stage 0, 46 (32.4%) were in stage I, 50 (35.2%) were in stage II, 23 (16.2%) were in stage III, and 1 (0.7%) was in stage IV. Ninety-two percent of women reported having bowel movements at least every day. When asked whether straining was required for them to have a bowel movement, 67% reported never or rarely,3% reported sometimes,1.6%) reported always. When asked whether they ever needed to help stool come out by pushing with a finger in the vagina or rectum, 77.0% reported never or rarely, 15.1% reported sometimes, (5.6%) reported usually, and (1.6%) reported always. No women had fecal incontinence, there were no clinically significant associations between any of the questions related to bowel function and severity of posterior vaginal prolapse. Conclusions: Women with uterovaginal prolapse frequently have symptoms related to bowel dysfunction but this is not associated with the severity of posterior vaginal prolapse.